Development of specialized multicellular 3D-Organotypic models to evaluate pathogenic mechanisms in non-alcoholic fatty liver disease (NAFLD) - Baptista, Catarina Borges (2024)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), affects over 30% of the global adult population. This condition includes a range of liver disorders, from steatosis (metabolic dysfunction-associated steatotic liver, MASL) to more severe stages such as metabolic dysfunction-associated steatohepatitis (MASH) and fibrosis, which can progress to cirrhosis and hepatocellular carcinoma. Effective therapies for MASLD are limited due to its multifactorial nature, which involves complex interactions among genetic, dietary, lifestyle, and metabolic factors. The interplay of processes which lead to lipotoxicity, insulin resistance, oxidative stress, mitochondrial dysfunction, ferroptosis, and inflammation in MASLD are not fully understood. Studies addressing MASLD have been hampered primarily due to the limitations of in vivo models and the lack of suitable in vitro models, particularly regarding the lack of accurate representation of chronic inflammation. This research project aimed to develop in vitro 3D hepatic models to address these gaps, specifically by creating (i) spheroids of cultured human hepatocytes and (ii) liver organoids that combine human hepatocytes with primary non-parenchymal cells. MASLD-like conditions could be induced in these models by exposing them to a combination of energy substrates. The resulting spheroids and organoids exhibited key MASLD characteristics, including steatosis, inflammation, oxidative and mitochondrial stress, and disrupted liver functions, such as dysregulated albumin-, bilirubin-, and cholesterol-homeostasis, along with elevated inflammatory markers. Notably, the organoid model, with its multiple liver cell types, demonstrated greater tolerance to hepatic functional disruption compared to hepatocyte spheroids, reflected by a more moderate and balanced inflammatory response. Overall, these findings demonstrate that the developed liver organoid serves as an effective 3D multicellular model capable of mimicking MASLD development and pathology. This model holds significant value for studying the pathophysiological pathways underlying MASLD, potentially informing future therapeutic strategies and aiding in the identification of diagnostic and prognostic biomarkers.